The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1509/jimk.11.1.13.20140
|View full text |Cite
|
Sign up to set email alerts
|

An International Marketing Manifesto

Abstract: In spite of important global inroads and successes scored by international marketing, the field stagnates in the eyes of academics, practitioners, and policymakers and is harshly attacked by activists. The people defending international marketing usually point to vague theoretical and long-term goals, whereas opponents serve up facile polemics, which acquire sympathies from the uninformed public. The authors postulate that the field of international marketing has already and can continue to make major contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
280
0
22

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(326 citation statements)
references
References 9 publications
8
280
0
22
Order By: Relevance
“…It is based on the same principles as those applied in developing a general concept of corporate expansion. This issue is widely discussed in literatures and does not require further attention in this papers (Ďaďo, 1997;Harrison et al, 2000;Czinkota & Ronkainen, 2004;Wiktor, Oczkowska, & Żbikowska, 2008;Nowakowski, 2008;Duliniec, 2009;Grzegorczyk, 2009;Hollensen, 2011;Kotler & Keller, 2012;Wiktor & Chlipała, 2012). …”
Section: An International Marketing Strategy In the Concept Of Corpormentioning
confidence: 91%
“…It is based on the same principles as those applied in developing a general concept of corporate expansion. This issue is widely discussed in literatures and does not require further attention in this papers (Ďaďo, 1997;Harrison et al, 2000;Czinkota & Ronkainen, 2004;Wiktor, Oczkowska, & Żbikowska, 2008;Nowakowski, 2008;Duliniec, 2009;Grzegorczyk, 2009;Hollensen, 2011;Kotler & Keller, 2012;Wiktor & Chlipała, 2012). …”
Section: An International Marketing Strategy In the Concept Of Corpormentioning
confidence: 91%
“…This applies particularly to pricing, as this mix related factor is the only revenue generating one [68]. Transfer pricing and export pricing are the most important price mix related factors for SMEs operating in B2B markets (Codita, 2010), serving in a standardised manner both as a tool for communication with the stakeholder (buyer) and as a competitive tool [82]. Therefore, pricing is considered to have a significant impact on marketing mix Standardization, particularly because SMEs usually use export pricing tools [73].…”
Section: Price and Product MIX Related Factorsmentioning
confidence: 99%
“…Backhaus and Voeth [83] found that both standard worldwide export prices and price Standardization between two B2B markets serve SMEs to create competitive advantage and to attract stakeholders. Studies in B2B markets further indicate that the implementation of price Standardization strategies by the use of sophisticated and systematic policies is indispensable for the SME"s success [82,84], as rapid development in communication technology and internet has made prices more transparent to stakeholders [83]. It is indispensable to standardise price decisions due to possible fluctuations in B2B demand, competitive environment and cost structures [79].…”
Section: Price and Product MIX Related Factorsmentioning
confidence: 99%
“…In this Bretton Woods II, countries must also recognize that they may not be able to get everything and win everywhere in negotiations. Perhaps key players need to seek to succeed mainly at their one most critical objective from four key areas: to grow, to make, to create economic activity, or to coordinate economic activity (Czinkota & Ronkainen 2012). The WTO also needs to reach out to nongovernmental organizations and try to include a broader range of domestic political actors (VanGrassek, 2013).…”
Section: The Future Global Framework and The Wtomentioning
confidence: 99%